Extra! Extra!: os jornaleiros e as bancas de jornais como espaço de disputas pelo controle da distribuição da imprensa e da economia política dos meios - Chagas, Viktor Henrique Carneiro de Souza (2013)
To paraphrase Robert Ezra Park, the news vendors have a history, but they also have a natural history. The evolution of the distribution and marketing model of printed publications, culminating in modern newsstands, points to negotiations involving the licensing for the operation of a commercial activity in urban public space. The newsstands themselves are therefore an area regulated by the government and operated by private enterprise, on a temporary basis. Why did it come to this model and what are its implications is one of the main issues addressed by this work. Among other points, this thesis aims to understand (1) the extent to which politicians and the public are able to act in the regulation of press freedom through control and supervision over the newsstands, (2) how professional sellers and distributors of newspapers and magazines mobilize themselves to confer visibility to their common demands and how their collective memory is built around these actions, (3) under what circumstances occur negotiations between these news vendors and men of the press, and how they are able to increase the penetration of certain printed vehicles with the public, acting decisively in shaping public opinion; and finally, (4) how important are the news vendors and the newsstands in the historical process of building political opinion on the news in the environment of large cities. In this sense, although evidenced by the current distribution model adopted by major cities in the country, the role of these actors as agents of cultural and political relevance in the production chain of print press has been subdued compared to analyses that focus on the technical or journalistic discourse, at most on the outskirts of theories of reception and popular culture appropriation – but never in this institution that has silently occupied our imaginary all these years: the newsstands.